Syntax comprehension in Persian-speaking students with ADHD - Armon Massoodi; Akram Ahmadi; Hanieh Haghjou; Marjan Larimian; Mohammadhasan Mazandarani; Hossein-Ali Nikbakht; Michelle Pascoe; Saba Ahmadzadeh; Faezeh Koohestani (BMC Psychiatry)
Abstract Background Syntax is one of the most intricate domains of language, and as such, offers valuable insights into language processing in typical and neurodiverse populations. The research aimed to compare syntactic comprehension in children aged 7–10 years with attention deficit hyperactivity disorder (ADHD) and typically developing (TD) children. Methods The Persian Syntax Comprehension Test (PSCT) was administered to 70 children diagnosed with ADHD and 70 TD peers. Syntactic items measured by this scale were graded in complexity, and results were compared across the two groups. Results A statistically significant difference (p < 0.001) between the two groups was found when comparing total PSCT scores that include simple, moderate, and complex structures. Among the obtained effect size values, the highest was for the difference between TD and ADHD children for complex syntactic structures (SMD = 0.72, 95% CI (0.38–1.06). In terms of the item-by-item comparisons, TD children performed significantly better on 58% of the items of the PSCT than children with ADHD. Conclusions Persian-speaking children with typical development in the 7–10-year age range outperformed children with ADHD on syntax comprehension. The most significant difference between the two groups was in the complex syntactic structures.